Analisis Kesesuaian Laporan Keuangan UMKM PT. Capture Data Teknologi Dengan SAK EMKM Berdasarkan Laporan Keuangan Tahun 2023–2024 (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the conformity of financial statement preparation of the MSME PT Capture Data Teknologi with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) for the financial statements of 2023–2024. Accurate and standard-compliant financial reporting is crucial for MSMEs to make informed business decisions and fulfill reporting requirements. The research employs a qualitative descriptive method with primary data collection through interviews, observations, and financial document analysis. The results indicate that PT Capture Data Teknologi has prepared financial statements largely in accordance with SAK EMKM regulations, although some areas still require improvement. This study provides insights into the level of MSME compliance with accounting standards and offers recommendations for enhancing financial reporting quality.